Persuasive Technology : 10th International Conference, PERSUASIVE 2015, Chicago, IL, USA, June 3-5, 2015, Proceedings - MacTavish, Thomas; Basapur, Santosh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 10th International Conference on Persuasive Technology, PERSUASIVE 2015, held in Chicago, IL, USA in June 2015. The 19 revised full papers and 5 revised short papers presented were carefully reviewed and selected from 41 submissions. The papers are grouped in topical sections on understanding individuals, empowering individuals, and understanding and empowering communities.
Involvement as working mechanism for persuasive technology -- Understanding persuasion and motivation in interactive stroke rehabilitation: A physiotherapists' perspective on patient motivation -- Formalizing Customization in Persuasive Technologies -- Understanding How Message Receivers Communication Goals are Applied in Online Persuasion -- What Makes You Bike? Exploring Persuasive Strategies to Encourage Low-Energy Mobility Preliminary Evaluation of Virtual Cycling System Using Google Street View -- Bet4EcoDrive: Betting for Economical Driving -- Persuasive Technology Based on Bodily Comfort Experiences: The Effect of Color Temperature of Room Lighting on User Motivation to Change Room Temperature -- BrightDark: A smartphone App utilizing e-fotonovela and text messages to increase energy conservation awareness -- Designing and Analyzing Swing Compass: A Lively Interactive System Provoking Imagination and Affect for Persuasion -- Does trigger location matter? The influence of localization and motivation on the persuasiveness of mobile purchase recommendations -- Adaptive Reminders for Safe Work -- For Your Safety: Effects of camera surveillance on safety impressions, situation construal and attributed intent Gender, Age, and Responsiveness to Cialdini s Persuasion Strategies -- Using Individual and Collaborative Challenges in Behavior Change Support Systems: Findings from a Two-Month Field Trial of a Trip Planner Application -- Towards a Framework for Socially Influencing Systems: Meta-Analysis of Four PLS-SEM Based Studies -- Attention - Influencing Communities of Practice with Persuasive Learning Designs -- Ethical Challenges in Emerging Applications of Persuasive Technology -- Influencing Retirement Saving Behavior with Expert Advice and Social Comparison as Persuasive Techniques -- A System Development Life Cycle for Persuasive Design for Sustainability -- Conforming to an Artificial Majority: Persuasive Effects of a Group of Artificial Agents -- A System s Self-Referential Persuasion: Understanding the Role of Persuasive User Experiences in Committing Social Web Users -- Advancing Typology of Computer-Supported Influence: Moderation Effects in Socially Influencing Systems.
Keywords: Computer science; Medical records -- Data processing; Multimedia systems; Computers and Society; User Interfaces and Human Computer Interaction; Health Informatics; Multimedia Information Systems; Information Systems Applications (incl. Internet).